The Haskins Society journal : studies in medieval history. - Morillo, Stephen; Korngiebel, Diane M. (Diane Marie) (Haskins Society Journal., 2007)
"Fruits of the most recent research on the worlds of the eleventh and twelfth centuries are presented in this collection. It features several articles on textual criticism with important revisions to controversial texts and their readings, as well as pieces on cultural history, an investigation into monetary history, and analyses of the legal and political mechanisms of conquest"--Www.boydell.co.uk